(untitled) (Globalization and Business, 2023)
Tourism is of particular importance to the world and many countries have chosen it as one of the main priorities of the country's development. Based on the accepted practice and the critical ecological background, each country recognizes the sustainable socio-economic development of tourism, developing concepts, systematic and complex approaches, drafting of state action programs, long-term perspectives and other aspects whose existence and implementation depends on state government. Therefore, this field can bring significant positive socio-economic results compared to other fields of economy. Rural tourism is a pleasant and useful combination of two positive events. The first is the entrepreneurial activity that can bring other benefits to the entrepreneur and the second village where the main holidays are housed in which the tourist can get interesting services such as sanitation, cognitive, aesthetic or other. According to the UNWTO, rural tourism will be more popular after the pandemic, as tourists avoid crowded places and prefer to relax in ecologically clean environment. This new trend will be a positive event and previously unpopular places among tourists will become a source of income. This in itself will help stimulate the development of rural tourism after the COVID-19 pandemic. The objective of the research is to study the opportunities of the rural tourism development after COVID-19 pandemic in Georgia and in mountainous regions of Adjara. Main questions discussed in this paper are: to analyze the employment opportunities for the population of rural areas; to foresee the possible secondary income, how to reduce the migration of rural population, especially the youth; possibility to supply the locally produced goods and service and to increase their awareness; possibilities to develop tourism-related industries. The joint efforts of government, municipal authorities, and business providers, with involvement of rural area inhabitants, are essential for the development of rural populated territories.